Accuracy of estimating total-tract fibre and protein fractions digestibilities using uNDF, uNDFom, and AIA markers, and their NIRS prediction potential in dairy sheep and goats - Tommaso Danese; Alberto Guerra; Marica Simoni; Giorgia Mantovani; Arianna Goi; Rosario Pitino; Alexandros Mavrommatis; Massimo De Marchi; Federico Righi; Eleni Tsiplakou (PLoS ONE, 2025)
This study investigated the use of uNDF, uNDFom, and acid insoluble ash (AIA) markers for estimating the total-tract and total-tract apparent digestibility (ttD and ttaD) of nutrients in dairy sheep and goats fed alfalfa hay and concentrate separately, and the potential of Near-Infrared Spectroscopy (NIRS) in predicting the estimated digestibility. A total of 180 faecal samples were collected from animals fed alfalfa hay and concentrate at varying ratios (F:C – 60:40, 50:50, 40:60). The samples underwent wet chemistry markers and nutrients analysis, to evaluate the digestibility of dry matter (DM), crude protein (CP), soluble CP, ash, neutral detergent fibre (NDF), acid detergent fibre (ADF), hemicellulose, cellulose, neutral detergent insoluble CP (NDICP), acid detergent insoluble CP (ADICP), and potentially degradable NDF (pdNDF). NIRS spectra acquisition was performed on the same samples and predictive models developed and tested. Compared to digestibility determined by total collection, results indicate that all the considered markers, namely uNDF, uNDFom and AIA tend to underestimate ttaD and ttD. Among the three makers, AIA resulted in the lowest recovery. Using uNDF as marker, NIRS predictive models showed almost adequate screening performance for ttADICPD and ttAshD, with a R²ExV values of 0.63 and 0.59, and RPDExV of 1.56 and 1.45, respectively. The uNDFom marker showed better performance for ttaDMD and ttADICPD preliminary screening, with R2ExV values of 0.55 and 0.62, and RPDExV values of 1.42 and 1.61, respectively. The study highlights that all the considered markers underestimate the nutrients digestibility, while uNDFom performed better concerning the NIRS calibration. Despite the encouraging results obtained, the NIRS accuracy in predicting digestibility traits in small ruminants remains poor, and further research are needed to explore its potential for nutrients ttD and ttaD measurement in sheep and goats.